2016
DOI: 10.1021/acsnano.6b03007
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Waterproof Self-Charging Power System for Harvesting Energy from Diverse Deformation and Powering Wearable Electronics

Abstract: A soft, stretchable, and fully enclosed self-charging power system is developed by seamlessly combining a stretchable triboelectric nanogenerator with stretchable supercapacitors, which can be subject to and harvest energy from almost all kinds of large-degree deformation due to its fully soft structure. The power system is washable and waterproof owing to its fully enclosed structure and hydrophobic property of its exterior surface. The power system can be worn on the human body to effectively scavenge energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 187 publications
(98 citation statements)
references
References 36 publications
0
98
0
Order By: Relevance
“…(1) High stretchablity (up to λ = 12.6 or strain ε = 1160%) and transparency (up to 96.2% average transmittance to full spectrum of visible light) are achieved, which are both much higher than those of previously reported stretchable and/or energy conversion devices using percolated conductive networks or ITO as the electrode materials ( 24 , 29 , 33 , 34 , 36 ). No performance degradation is observed at stretched states as well.…”
Section: Discussionmentioning
confidence: 94%
“…(1) High stretchablity (up to λ = 12.6 or strain ε = 1160%) and transparency (up to 96.2% average transmittance to full spectrum of visible light) are achieved, which are both much higher than those of previously reported stretchable and/or energy conversion devices using percolated conductive networks or ITO as the electrode materials ( 24 , 29 , 33 , 34 , 36 ). No performance degradation is observed at stretched states as well.…”
Section: Discussionmentioning
confidence: 94%
“…Yi et al reported a method for TENGs and highly deformable and stretchable self‐powered sensors 72. A shape‐adaptive triboelectric nanogenerator (saTENG) unit with conductive liquid as electrodes can be used to harvest various mechanical energy effectively in different motions (Figure 7D).…”
Section: Materials and Device Designmentioning
confidence: 99%
“…Though the TENG and batteries/capacitors cannot share electrodes, they can be designed to share the package or substrate, or the electrification dielectric layer of the TENG could possibly serve as the substrate/package of the batteries/supercapacitors. In this way, all‐in‐one SCPSs have been reported …”
Section: Scpss With Mechanical Energy Harvestingmentioning
confidence: 89%